Variety of Coastal Ornaments in Aceh: Aesthetic Phenomena in the Continuation of History and Culture - Bukhari Bukhari; Aulia Rahman; Mufti Riyani (Budapest International Research and Critics University, 2020)
Focusing on the study of historical artifacts of art found in the Aceh Coastal region, this study seeks to analyze ornamental diversity as an aesthetic phenomenon that has a meaningful relationship with 1. Continuation of history, 2. Links in the search for cultural identity, and 3 Balancing cultural values in Acehnese society . Throughout history, the art of embroidering gold threads, woven silk fabrics, stabbing weapons, jewelry art, and wood carvings have been the hallmark of Aceh beach crafts that in their development consistently used their identity motifs. The intended identity motif is a motif that shows the cosmopolitanism of Aceh regarding pre-Islamic cultural influences and influences originating from friendly countries. The diplomatic relations which brought the influence of Persia and the Moghul dynasty from India occurred at the golden peak of Aceh's art history, especially during the times of Iskandar Muda and Iskandar Thani, although in the end, the clearest artistic trend emerged, namely all Islam. Aceh's design patterns in a stylish form become geometric shapes. The characteristic of decoration in the coastal communities of Aceh is influenced by Arabic concepts, is the development of a sense of beauty that is free from natural myths and is done by developing abstract patterns taken from floral motifs, foliage shaped and polygon shapes as a process of balancing cultural values.